2014
DOI: 10.1590/s2236-89062014000100009
|View full text |Cite
|
Sign up to set email alerts
|

Morfologia de esporos de pteridófitas do Parque Estadual das Fontes do Ipiranga (São Paulo, Brasil). Família: 21-Tectariaceae

Abstract: -(Morphology of spores of pteridophyte from the Parque Estadual das Fontes do Ipiranga (São Paulo, Brazil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
1
0
4
Order By: Relevance
“…The color of the spores of the genus is a characteristic not mentioned by any of the authors in previous works. Only Lebrão et al (2014) illustrate with LM the acetolyzed spores of 3 species of Ctenitis from central Brazil, where it is observed that they are light brown in color. In any case, most of the species that inhabit the In the illustrations of these authors, as in those of this work, it can be seen that the spines are coarse and have a broad base and usually broken apex, revealing that they are hollow inside.…”
Section: An Acad Bras Ciencmentioning
confidence: 99%
“…The color of the spores of the genus is a characteristic not mentioned by any of the authors in previous works. Only Lebrão et al (2014) illustrate with LM the acetolyzed spores of 3 species of Ctenitis from central Brazil, where it is observed that they are light brown in color. In any case, most of the species that inhabit the In the illustrations of these authors, as in those of this work, it can be seen that the spines are coarse and have a broad base and usually broken apex, revealing that they are hollow inside.…”
Section: An Acad Bras Ciencmentioning
confidence: 99%
“…Entre las contribuciones de estudios palinológicos de especies americanas podemos mencionar a Moy (1988) que estudia las esporas de 5 especies de Ctenitis principalmente del norte de Sudamérica y Lebrão et al (2014) que analizaron 3 especies del mismo género en el centro de Brasil. Diversos trabajos sobre las esporas de Dryopteris que crecen en Norteamérica han sido llevados a cabo por Britton (1968Britton ( , 1972aBritton ( , 1972b) y Britton y Jermy (1974).…”
Section: Presentación Del Temaunclassified
“…Los últimos aportes sobre las esporas del género Ctenitis fueron realizados por Lebrão et al (2014) quienes describieron con microscopio óptico las esporas de C. aspidioides, C. distans y C. falciculata para Brasil.…”
Section: Antecedentes De Estudios Palinológicosunclassified
See 2 more Smart Citations